Sinergisitas Pembangunan Berkela Studi terhadap Kebijakan Pengentasan Kemiskinan di Aceh: Synergy, Sustainable Development, Policy, Poverty - Zamharira, Cut; Khalil, Zakki Fuad; Nufus, Hayatun (Jurnal Transformasi Administrasi, 2024)
This research examines extreme poverty in Aceh, particularly in North Aceh Regency, where the poverty rate reaches 16.86%, exceeding both national and provincial averages. The study aims to assess the synergy of government policies in poverty alleviation and the government's strategies in promoting sustainable development. The research method utilizes primary data collected through interviews and Focus Group Discussions (FGD) with the government of North Aceh Regency, as well as secondary data from the Central Statistics Agency and relevant institutions. The findings indicate that the synergy among stakeholders in sustainable development remains weak, with each institution operating independently without effective coordination. Furthermore, the legal framework related to poverty alleviation has not been ratified, and the formation of a coordination team has not been implemented. In conclusion, stronger synergy between the government and stakeholders is needed to improve sustainable poverty alleviation policies in Aceh.